2023
DOI: 10.37934/araset.30.1.1530
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and Numerical Simulation of Surface Pressure of an Oscillating Wedge at Hypersonic Mach Numbers and Application of Taguchi's Method

Abstract: This paper aims to estimate the surface pressure of a wedge at hypersonic Mach numbers at a considerable angle of incidence. The Ghosh similitude, corresponding strip theory, and piston theory are used to determine the pressure distribution analytically, and the results are compared to those of the CFD analysis. The theory is valid when the shock wave is attached to the leading edge of the nose of the wedge. Pressure on the windward surface was considered in the analysis. The pressure on the Lee surface is neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The results show that SST combined with the transition model accurately predicts the flow conditions that vary from laminar to turbulent transitions due to infringing jets in the wall jet region [13]. A recent conducted by study Shamitha et al, [14] examined the surface pressure of a wedge at a hypersonic Mach number. The study reported that the dimensionless static pressure at the nose of the wedge only undergoes minimal changes for smaller wedge angles and Mach numbers.…”
Section: Introductionmentioning
confidence: 89%
“…The results show that SST combined with the transition model accurately predicts the flow conditions that vary from laminar to turbulent transitions due to infringing jets in the wall jet region [13]. A recent conducted by study Shamitha et al, [14] examined the surface pressure of a wedge at a hypersonic Mach number. The study reported that the dimensionless static pressure at the nose of the wedge only undergoes minimal changes for smaller wedge angles and Mach numbers.…”
Section: Introductionmentioning
confidence: 89%
“…Using ANSYS workbench the meshing and modeling are completed and for the analysis and post-processing, ANSYS Fluent was used. To obtain the correct and precise numerical results, the structured mesh is used [31][32][33][34][35][36][37][38][39][40][41][42][43]. The Mach numbers span interval taken into the account as 5.0, 7.0, 9.0, 10.0, and 15.0 for the analysis together with semi-cone angles as 5°, 10°, 15°, 20° and 25°.…”
Section: Methodology 21 Cfd Analysismentioning
confidence: 99%
“…The minimal duct length for the flow to stay attached is 2D for nozzle pressure ratios greater than 5, according to research on convergent-divergent nozzles utilizing microjets at Mach 2.1 [22]. Shamitha et al, [23] examined the wedge's surface pressure for a large angle of incidence at hypersonic Mach number. According to the findings, surface pressure increases as hypersonic Mach numbers and angle of incidence increase.…”
Section: Active Controlmentioning
confidence: 99%